The influence of internal spatial coupling characteristics of blue-green space on cooling benefit in metropolitan areas: Evidence form Hangzhou, China - Qianru Lu; Weifeng Qi; Dongye Yang; Mingyu Zhang (Environmental and Sustainability Indicators)
The phenomenon of urban thermal environment has become increasingly serious recently, with blue-green spaces playing a crucial role in cooling urban warming. However, the synergistic cooling effects of blue and green spaces, treated as distinct entities with unique cooling mechanisms, have not been extensively explored. This study addresses this gap by examining the internal spatial coupling characteristics of blue and green spaces and their impact on cooling benefit under varying high-temperature conditions and development densities in Hangzhou, China. This study uses the area-weighted cooling intensity and the mean land surface temperature to reflect the cooling benefit, and proposes an evaluation system for spatial coupling characteristics including internal scale relationships, distance relationships, and morphological relationships, while considering the built environment and integrated spatial features as control variables. Using stepwise multiple linear regression and geographically weighted regression, the study analyzes the correlation between these characteristics and cooling benefit across four days using 4 global datasets and 16 local datasets. Results indicate that spatial coupling significantly impact its cooling effects, with internal scale relationships having the greatest impact. The influence of spatial coupling relationships varies across different land-use densities, with more pronounced effects under typical high-temperature conditions compared to extreme heat. These findings offer urban planners valuable insights into optimizing the spatial relationship of blue-green spaces, helping to maximize their cooling benefit in limited space resource in metropolitan, ultimately enhancing urban resilience to climate change.